Factors Affecting Intellectual Capital Disclosure and Company Value - Arda Raditya Tantra (LifeSciFi, 2018)
This study examined the effect of profitability, firm age, firm size, leverage, earnings growth and profit growth on the intellectual capital disclosure (ICD) and the effect of intellectual capital disclosure on firm value. Sample in this research was obtained from 78 manufacturing companies listed on the Indonesia Stock Exchange with specific observations to the financial data in the period 2012-2015. By using Structural Equation Modeling (SEM) analysis techniques operated through the AMOS Version 21 program, the results show that profitability, and growth have a positive and significant effect on intellectual capital disclosure. Furthermore, intellectual capital disclosure as a mediating variable has an significant influence on firm value. Other findings indicate that the variables of company age, firm size, and leverage did not significantly affect intellectual capital disclosure. The findings of this study underline the importance of creating and strengthening intellectual capital disclosure in public companies in Indonesia.